Central nervous system metastases in advanced breast cancer patients treated with trastuzumab - Duchnowska, Renata; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2006)
Amplification or overexpression of HER2 receptor is present in 20-30% of invasive breast cancers and in 60% of intraductal cancers. Patients with HER2 gene aberrations have more aggressive disease, frequent disease recurrence and a shorter survival. Trastuzumab (herceptin) is a monoclonal antibody selectively directed against the HER2 epidermal growth factor receptor. Adding herceptin to therapy of metastatic breast cancer patients with overexpression and/or amplification of HER2 has increased complete and partial response rates, as well as prolonged time to progression and overall survival. A common failure site during trastuzumab therapy is brain. Brain dissemination is probably related to the lack of CNS penetration of trastuzumab, a consequence of its high molecular weight (145 kDa). Another hypothesis includes improved systemic disease control outside the brain, leading to prolonged survival without brain protection (a ”sanctuary site”). It was also postulated that HER2 overexpression and/or amplification might predispose to brain metastases. The aim of this article is to discuss the pathomechanism of this phenomenon and its clinical implications.